Challenges of ancient DNA preservation in Finland: A report on unsuccessful samples - Nordfors, Ulla; Peltola, Sanni; Kuusela, Jari-Matti; Majander, Kerttu; Saari, Nelli-Johanna; Salo, Kati; Onkamo, Päivi (The Archaeological Society of Finland, 2026)
Ancient DNA (aDNA) research has rapidly expanded our understanding of past populations, yet its success remains highly dependent on biomolecular preservation. This article presents negative sampling outcomes from 85 individuals in Finland, sampled between 2017 and 2022. These individuals represent sampling efforts that failed to yield data for human population genetic analyses, corresponding to a success rate of approximately 44%. The failed dataset includes samples from a wide temporal and geographical range, from Bronze Age contexts to post-medieval burials, and notably, some of Finland’s most iconic archaeological individuals. Our findings align with previous studies and show that the petrous part of the temporal bone and teeth consistently outperform other skeletal elements in human DNA preservation. Preservation also varied by region, and possibly also by burial environment and post-excavation storage history.